Tênues relações: uma investigação da estrutura formal na casa contemporânea brasileira - Cabral, Tamires Oliveira (2016)
The formal variety that characterizes contemporary architectural production tends to make its understanding and eventual classification more difficult, which in turn makes the identification and analysis of its elements and configuration something challenging. From this perspective, this article’s goal is to analyze the formal structure of houses designed by three Brazilian firms, which are located in different contexts. As a result, we expect the thesis to identify recurrence patterns and exceptionalities among the analyzed projects, and to foster the investigation of Brazilian houses from the 21st century.